The Emergence of Blockchain Technology in Ubiquitous Computing - Parthasarathy, P.D; Vijayakumaran, Vinod (International Journal of Computer Sciences and Engineering, 2025)
Blockchain Systems and Ubiquitous computing are changing the manner we work together and lead our lives. A standout amongst the most imperative utilizations of the Blockchain technology is in automation processes, digital assistants and Internet-of-Things (IoT). Machines have so far been constrained in ability primarily because they have restricted capacity to exchange value. Any monetary exchange of value which is of significant worth must be supervised by humans or human based centralized ledgers. Blockchain technology changes all that. It allows machines to have unique identities and hence a virtual presence. Blockchain technology even allows for automated verification by the network of machines itself. It permits machines to exchange value and introduce the element of discretion in the hands of Machines. This can form the basis for ultimately developing IoT going on to Artificial Intelligence. This paper aims to investigate and expound couple of most impactful use-cases of blockchain technology in ubiquitous computing/omnipresent processing